A broad-spectrum novel bacteriocin produced by Lactobacillus plantarum SHY 21–2 from yak yogurt: Purification, antimicrobial characteristics and antibacterial mechanism. (May 2021) - Peng, Shudong; Song, Jiajia; Zeng, Weiyou; Wang, Hongwei; Zhang, Yu; Xin, Jinwei; Suo, Huayi
Abstract: This research aimed to find a natural biological preservative that inhibits harmful bacteria in the food production process. We screened a bacteriocin-producing Lactobacillus plantarum SHY 21–2, which was isolated from yak yogurt. The bacteriocin was purified by salting out, AKTA purifier 10 and reversed-phase high-performance liquid chromatography (RP-HPLC). The LC-MS/MS analysis revealed that the molecular weight of bacteriocin was 1362.84 Da and the predicted the amino acid sequence was RPNEPRLLLPR. This strain produced a novel IId bacteriocin and named plantaricin LP 21–2. LP 21–2 was heat-resistant and still had 96% antibacterial activity after being exposed to 121 °C for 15 min. LP 21-2 had obvious antibacterial activity at pH 2–5 and could be completely inactivated by pepsin, trypsin, and papain. LP 21-2 had a broad antimicrobial spectrum against on Gram-positive bacteria, Gram-negative bacteria and fungi, including Staphylococcus aureus ATCC25923, Salmonella typhi CMCC50071 and Saccharomyces cerevisiae ATCC9763. The minimal inhibitory concentration (MIC) of LP 21–2 on Staphylococcus aureus ATCC 25923 was 0.18 mg/ml. Analyzed by scanning electron microscopy and transmission electron microscopy, LP 21–2 induced pore formation in cell membranes and caused cytoplasmic leakage to kill bacteria. These results indicate that plantaricin LP 21-2 has potential as a bioprotective agent in food. Highlights: A novel Ⅱd bacteriocin LP 21–2 was purified. LP 21–2 was a broad-spectrum, heat-resistant and protease-inactivated bacteriocin. The antibacterial mechanism of LP 21–2 was acted on cell membrane pore forming and leads to cell death.